2011
DOI: 10.1080/08952841.2011.540484
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Self-Esteem in a Multiethnic Sample of Women Over 50 at Risk for HIV

Abstract: Self-esteem is linked to high-risk behaviors in other populations but has not been examined in women aged 50 and older. This study explored how self-esteem is related to variables that can influence high-risk sexual behaviors in women over 50. A multiethnic community-based sample of 572 women aged 50 and older completed an anonymous questionnaire on sexual behaviors, sociodemographic characteristics, and psychosocial measures relevant to midlife and older women. Regression analysis showed sensation-seeking, HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…As a result, risk behaviors may go unnoticed (Jacobs & Kane, 2011;Longfield et al, 2004). It is believed that those who do not have a medical provider, an important external support, increases the odds that any HIV risk behavior can go unnoticed.…”
Section: Personal Doctormentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, risk behaviors may go unnoticed (Jacobs & Kane, 2011;Longfield et al, 2004). It is believed that those who do not have a medical provider, an important external support, increases the odds that any HIV risk behavior can go unnoticed.…”
Section: Personal Doctormentioning
confidence: 99%
“…Subjective well-being affects individuals socially, physically, and economically, influencing their physical and mental health (Pangman & Seguire, 2000) and in terms of HIV risk behavior, can dictate the dynamics of relationships (Jacobs & Kane, 2011), gender role context (Logan et al, 2002), and interpersonal power (Jacobs & Kane, 2011). It has been suggested that those who report experiencing a lower quality of life engage in more risk taking behaviors, and in combination with other vulnerable characteristics, that risk is higher (Aronowitz et al, 2007;El-Bassel et al, 2009).…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations